IMPLEMENTASI PELAYANAN ADMINISTRASI AKADEMIK IKIP PGRI BOJONEGORO BERBASIS ONLINE - Dwiyanti Septi Sukmasari (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2018)
The Implementation for application of information technology in higher education is one form of change in the process of academic administration services to students so that the student registration process is more effective and efficient. In relation to the use of information technology for the management of student administrative academic documents, IKIP PGRI Bojonegoro has made changes to the academic administration system from a manual document management system to an online-based student administration management system, namely management of information technology-based document administration through the internet. This study focuses on the problem of how the effectiveness of online academic administration services of IKIP PGRI Bojonegoro students and what factors influence the effectiveness of online academic administration services of IKIP PGRI Bojonegoro students with descriptive qualitative research methods, and theory used is e-government and information systems. The findings of this study obtained that the online academic administration services of IKIP PGRI Bojonegoro students are actually very good for meeting the academic needs of students. Students also understand the ways or steps to access the online academic administration portal.